2002
DOI: 10.1086/341381
|View full text |Cite
|
Sign up to set email alerts
|

Variable Stars in the Unusual, Metal-rich Globular Cluster NGC 6388

Abstract: We have undertaken a search for variable stars in the metal-rich globular cluster NGC 6441 using time-series BV photometry. The total number of variables found near NGC 6441 has been increased to ∼ 104, with 48 new variables being found in this survey. A significant number of the variables are RR Lyrae stars (∼ 46), most of which are probable cluster members. As was noted by Layden et al. (1999), the periods of the fundamental mode RR Lyrae are unusually long compared to field stars of similar metallicity. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 104 publications
(199 reference statements)
3
112
0
Order By: Relevance
“…Long-period (P0.82-0.85 days) RRLs are quite rare in Galactic globulars. Several of them have also been identified in two peculiar bulge metal-rich globulars-NGC 6388, NGC 6441 (Pritzl et al 2001(Pritzl et al , 2002)-and in the Galactic field (Wallerstein et al 2009). Whether they are truly long-period RRLs or shortperiod Type II Cepheids (TIICs) is still a matter of lively debate (Marconi et al 2011;Soszyński et al 2011).…”
Section: Period Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-period (P0.82-0.85 days) RRLs are quite rare in Galactic globulars. Several of them have also been identified in two peculiar bulge metal-rich globulars-NGC 6388, NGC 6441 (Pritzl et al 2001(Pritzl et al , 2002)-and in the Galactic field (Wallerstein et al 2009). Whether they are truly long-period RRLs or shortperiod Type II Cepheids (TIICs) is still a matter of lively debate (Marconi et al 2011;Soszyński et al 2011).…”
Section: Period Distributionmentioning
confidence: 99%
“…Moreover, they seem to belong to two different sub-groups (if we exclude a few long-and short-period outliers): (a) shortperiod-with periods ranging from ∼0.30 to ∼0.36 days and visual amplitudes ranging from a few hundredths of a magnitude to a few tenths; (b) long-period-with periods ranging from ∼0.36 to ∼0.45 days and amplitudes clustering around AV∼0.5 mag. With the only exception of the metalrich clusters NGC 6388 (Pritzl et al 2002), NGC 6441 (Pritzl et al 2001), and V70 in M3 (Jurcsik et al 2012), ω Cen is the only GGC where long-period RRc are found (Catelan 2004b). Theoretical and empirical evidence indicates that the RRc period distribution is affected by metallicity (Dall'Ora et al 2003).…”
Section: Bailey Diagrammentioning
confidence: 99%
“…-M80, M13, M3 -This is the popular cluster triplet at intermediate metallicity with different HB morphologies, including red clumps, gaps, and blue tails (see, e.g., Ferraro et al 1997Ferraro et al , 1998Dalessandro et al 2013a (Rich et al 1997;Pritzl et al 2001Pritzl et al , 2002Pritzl et al , 2003Busso et al 2007;Dalessandro et al 2008). …”
Section: Observations Data Reduction and Photometric Analysismentioning
confidence: 99%
“…Beside the red clump, which is a typical feature of metal-rich stellar populations, the HB clearly shows an extended blue tail (BT), first noticed by Rich et al (1997) and by Piotto et al (1997). Among a total of 1763 HB stars counted in the HST sample, five subpopulations can be distinguished (see xx 3.1.1 and 3.1.2 for details): (1) the red HB (RHB) population, consisting of 1418 stars grouped in the red clump; (2) 15 RR Lyrae variables, which we identified by cross-correlating the positions in our catalog with Lanzoni et al (2007c) those published by Pritzl et al (2002); 7 (3) 267 blue HB (BHB) stars; (4) 26 extreme HB (EHB) stars; and (5) 37 blue hook (BHk, to avoid confusion with BH for black hole) stars. Several previous works have shown that the HB morphology in NGC 6388 is complex.…”
Section: The Hst Samplementioning
confidence: 99%